PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DALAM PEMBELAJARAN MATEMATIKA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK DI SEKOLAH DASAR - Dina Mardiana; Rayi Siti Fitriani; Atep Lesmana (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
Based on the research to understand of influence the implementation and increased use of learning model contextual teaching and learning of the understanding ability a mathematical conception of elementary school grade 3.This research triggered by the importance of the understanding ability a mathematical conception for learners of elementary school grade 3 .The study is done in SDN 2 Sukajaya for year academic 2017 / 2018. The method used in this research is a method of quantitative with design of quasi experiment design. The population of the research is all students from SDN 2 Sukajaya grade 3. Sampling technique used namely sampling technique saturated sampling technique this is all population used as samples for research. Sampling techniques used the techniques of sampling saturated, this sampling techniques used in the sample of the population. The data technique on this research using objective test. The result of this research is indicates there an effect from the ability of understanding between class a mathematical conception of the experiments with contextual kind of classroom teaching and learning and control group with direct instruction method. The results of the t-test at 5% significance level obtained significance Count between 0002 ≤ 0.05. As for the improved results obtained from U at 5% significance level obtained significance Count between 0.006 ≤ 0.05, so it can be revealed learning by Implementation of Contextual learning method of Teaching and Learning effect in improving the ability of understanding of mathematical concepts